Resolusi Pembiayaan Murabahah Bermasalah: Studi Kasus Mitigasi Risiko Berbasis Modal Sosial pada KSPPS X - Afridatul Fikriyah; Abdul Latip (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to identify the triggering factors and evaluate the effectiveness of resolution strategies and risk mitigation for non-performing murabahah financing at KSPPS X, amid the challenges of a Non-Performing Financing (NPF) ratio that remains above the regulatory safety threshold, reaching 13.04% in 2024. Utilizing a descriptive qualitative case study approach, data were gathered through in-depth interviews with management and analysis of internal collectibility report documents for the 2022–2024 period. The research findings indicate that KSPPS X constructs a financial security perimeter through a three-pillar strategic architecture: preventive (5C feasibility underwriting and pre-contract education), curative (sharia-compliant 3R restructuring: Rescheduling, Reconditioning, Restructuring), and solutive. An interesting finding in this study highlights the optimization of social capital in the final solutive stage. The cooperative strictly rejects the use of external debt collectors and instead involves local authority figures (RT, RW, and community leaders) through a deliberation mechanism to execute collateral liquidations to safeguard the institution's dignity and maintain social harmony. In conclusion, this tiered strategic combination has proven functional in reducing reputational risk and curbing bad debts. However, the system's overall effectiveness still leaves structural weaknesses due to human resource quantitative constraints and a manual daily monitoring method stemming from its institutional transformation into a fully sharia-compliant system. Therefore, this study recommends that management immediately modernize its information technology infrastructure through the implementation of a digital early warning system to optimize long-term financial soundness.